The talent paradox: Why is it fair to reward talent but not luck? - Björn Bartling; Alexander W. Cappelen; Ingvild L. Skarpeid; Erik Ø. Sørensen; Bertil Tungodden (University of Zurich, Department of Economics, 2025)
This paper investigates how people differentiate between inequality caused by talent and inequality caused by luck in a large-scale study of the US population. We establish that people distinguish significantly between inequality due to luck and inequality due to talent, even when controlling for their beliefs about the extent to which these factors are within individual control. We refer to this as the "talent paradox". In a novel experiment, we provide evidence suggesting that individuals are more accepting of inequality caused by talent than by luck because the benefits of talent are only realized if one acts upon it. In contrast, manipulating the extent to which talent is perceived as a personal characteristic has no effect on inequality acceptance. Our findings provide new evidence on the nature of people's fairness views that sheds light on the political debate on the acceptability of inequality in society.
Keywords: C9; D63; 330; talent; luck; effort; fairness; inequality